Mating populations of the fusarium fujikuroi species complex (FFSC) associated with wild grasses (gramineae) in Peninsular Malaysia / Nor Azliza Ismail ... [et al.] - Ismail, Nor Azliza; Azuddin, Nurul Farizah; Rosli, Hafizi; Salleh, Baharuddin (Universiti Teknologi MARA Cawangan Pahang, 2021)
The present study sought to explore the mating populations (MPs) of the Fusarium fujikuroi species complex (FFSC) associated with asymptomatic wild grasses throughout Peninsular Malaysia. Results demonstrated that species in the FFSC associated with wild grasses were less diverse of which only two species were obtained, namely F. sacchari (10 isolates) and F. proliferatum (20 isolates). Of 30 isolates, 26 were found to be fertile and produced eight-celled ascospores in perithecia, whereas the remaining four isolates were not, hence, considered as infertile. Two MPs were recognised i.e. MP-B (F. sacchari; 10 isolates) and MP-D (F. proliferatum; 16 isolates). Both mating types, namely MAT-1 and MAT-2 were present, but the ratio was somewhat uneven (~2:1). Based on the uneven ratio of mating types and different sampling locations, sexual reproduction among isolates obtained in this study is not possible under the field condition. Reproduction using sexual means is insignificant for the survivability of Fusarium species in nature. Also, the findings further confirmed that F. sacchari and F. proliferatum are indeed two main species in the Asian Clade regardless of their hosts.